Identification of a thalidomide derivative that selectively targets tumorigenic liver progenitor cells and comparing its effects with lenalidomide and sorafenib - Woo, K.; Stewart, S.; Kong, G.; Finch-Edmondson, M.; Dwyer, B.; Yeung, S.; Abraham, L.; Kampmann, S.; Diepeveen, L.; Passman, A.; Elsegood, Caryn; Tirnitz-Parker, Nina; et al. (Elsevier Masson, 2016)
© 2016 Elsevier Masson SASBackground & aims The availability of non-tumorigenic and tumorigenic liver progenitor cell (LPC) lines affords a method to screen putative anti-liver cancer agents to identify those that are selectively effective. To prove this principle we tested thalidomide and a range of its derivatives and compared them to lenalidomide and sorafenib, to assess their growth-inhibitory effects. Methods Cell growth, the mitotic and apoptotic index of cell cultures were measured using the Cellavista instrument (SynenTec) using commercially available reagents. Results Neither lenalidomide nor thalidomide (100 µM) affected tumorigenic LPCs but killed their non-tumorigenic counterparts. Sorafenib arrested growth in both cell types. All but two derivatives of thalidomide were ineffective; of the two effective derivatives, one (thalidomide C1) specifically affected the tumorigenic cell line (10 µM). Mitotic and apoptotic analyses revealed that thalidomide C1 induced apoptotic cell death and not mitotic arrest. Conclusions This study shows that screens incorporating non-tumorigenic and tumorigenic liver cell lines are a sound approach to identify agents that are effective and selective. A high throughput instrument such as the Cellavista affords robust and reproducible objective measurements with a large number of replicates that are reliable. These experiments show that neither lenalidomide nor thalidomide are potentially useful for anti-liver cancer therapy as they kill non-tumorigenic liver cells and not their tumorigenic counterparts. Sorafenib in contrast, is highly effective, but not selective. One tested thalidomide derivative has potential as an anti-tumor drug since it induced growth arrest; and importantly, it selectively induced apoptotic cell death only in tumorigenic liver progenitor cells.